Susceptibility of subregions of prefrontal cortex and corpus callosum to damage by high-dose oxytocin-induced labor in male neonatal mice. - Eri Kitamura (Public Library of Science (PLoS), 2021)
Induction and augmentation of labor is one of the most common obstetrical interventions. However, this intervention is not free of risks and could cause adverse events, such as hyperactive uterine contraction, uterine rupture, and amniotic-fluid embolism. Our previous study using a new animal model showed that labor induced with high-dose oxytocin (OXT) in pregnant mice resulted in massive cell death in selective brain regions, specifically in male offspring. The affected brain regions included the prefrontal cortex (PFC), but a detailed study in the PFC subregions has not been performed. In this study, we induced labor in mice using high-dose OXT and investigated neonatal brain damage in detail in the PFC using light and electron microscopy. We found that TUNEL-positive or pyknotic nuclei and Iba-1-positive microglial cells were detected more abundantly in infralimbic (IL) and prelimbic (PL) cortex of the ventromedial PFC (vmPFC) in male pups delivered by OXT-induced labor than in the control male pups. These Iba-1-positive microglial cells were engulfing dying cells. Additionally, we also noticed that in the forceps minor (FMI) of the corpus callosum (CC), the number of TUNEL-positive or pyknotic nuclei and Iba-1-positive microglial cells were largely increased and Iba-1-positive microglial cells phagocytosed massive dying cells in male pups delivered by high-dose OXT-induced labor. In conclusion, IL and PL of the vmPFC and FMI of the CC, were susceptible to brain damage in male neonates after high-dose OXT-induced labor.